Removal of Cadmium Ions from Wastewater by Batch Experiments - Abed M., Eman; Faisal M., Lahieb; Swadi T., Younis (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Adsorption experiments were carried out using two different low-cost sorbent materials, date seeds and olive seeds. These sorbents used as a single phase (not as mixture) to remove cadmium ions from simulated wastewater by adsorption process. The equilibrium time was found at 2 hr. The experiments include different parameters such sorbent type and weight and contact time. It was found that both of olive seed and date seed have approximately the same adsorption capacity (qm) with 15.644 mg/g and 15.2112 mg/g, respectively. Equilibrium isotherms and kinetic studies have been carried out. Langmuir isotherm model better fits the experimental data compared with the Freundlich isotherm for olive seed, while Freundlich isotherm fits for date seed .A pseudo-second order kinetic model was appropriate to the experimental data for both seeds. It can be concluded that the olive seed and date seed could be a good sorbent for the removal of cadmium ions from wastewater.